Optimization of Adsorption of Tetracycline as Water Contaminant onto Solid Supported ZnO Systems Using Point of Zero Charge - Tweir, Rola Fathi Mohammed (جامعة النجاح الوطنية, 2020)
Water pollution is a difficult challenge that faces the world nowadays. Pollutions may be caused by pesticides, fertilizers, industrial discharge, domestic waste and pharmaceutical residue. Contamination of surface water by pharmaceuticals is considered a serious environmental threat, which makes their treatment from water a vital issue in researches. Adsorption, a simple, economic, safe and efficient process, is one method used in water treatment. In this work, adsorption of a widely used antibiotic, Tetracycline (TC), was studied using commercial ZnO, Montmorillonite (MONT), Kaolinite (KANT), prepared ZnO@MONT and ZnO@KANT as low-cost, environmentally friendly and effective adsorbents. ZnO nano-sized adsorbent was supported on MONT (a clay with high surface area) and KANT (a clay with good stability) to improve TC adsorption capacity and to facilitate adsorbent recovery from water. Characterization of commercial ZnO, MONT, KANT, prepared ZnO@MONT and ZnO@KANT was made using X-ray diffraction (XRD) and scanning electron microscopy (SEM) equipment. Zero charge point (ZCP) was determined for each adsorbent using pH drift method. Effects of different parameters on the TC adsorption process were studied, such as: solution pH (3-11 pH range), adsorbent type, contact time and TC concentration. ZCP values were 9.8, 4.5 and 7.5 for commercial ZnO, MONT and KANT, respectively, and 7.2 for the prepared composites (ZnO@MONT and ZnO@KANT). The experimental data showed that MONT is the best adsorbent with maximum adsorption capacity of 125 mg/g at neutral pH following the Freundlich isotherm. KANT and ZnO@MONT also followed the Freundlich isotherm. ZnO and ZnO@KANT followed the Langmuir isotherm. Kinetic study showed that the pseudo-second order model is the most representing model for each adsorbent. Equilibrium adsorption time was ~120 min. The optimum pH range was between (5-7) that gives the best adsorption, affected by the ZCP of each adsorbent and the surface charge of TC at this pH. The opposite charges between adsorbent and adsorbate cause an electrostatic attraction which increase the adsorption capacity. Increasing of TC concentration causes an increase in adsorption.
دراسة امتزاز الملوث تتراسايكلين من الماء باستخدام أكسيد الزنك المثبت على السطوح الصلبة بطريقة قياس شحنة السطح المتعادلة